1983
DOI: 10.1007/bf00123307
|View full text |Cite
|
Sign up to set email alerts
|

The use of telotrisomics for centromere mapping in Arabidopsis thaliana (L.) Heynh.

Abstract: For 4 different telotrisomics of Arabidopsis thaliana segregation ratios are given for a number of genes located on the extra telocentric chromosome. These data are discussed in relation to the meiotic behaviour expected with telotrisomics. By relating the frequencies of recombinants in the progeny of heterozygous telotrisomics with the map position of the loci, the centromere position may be determined (not only in respect to order, but also in respect to distance). Chromosome arms may differ with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 12 publications
2
31
0
1
Order By: Relevance
“…The 180-bp array RCEN3 marker falls within this interval, ∼5.5 cM south of the GL1 genetic marker. Finally, the telocentric strategy indicated that centromere 5 is located in an ∼11-cM window between morphological markers ga-3 and tt-2 (Koornneef 1983;Hauge et al 1993). Neither of these markers is present on the current recombinant inbred genetic map, yet the localization of the 180-bp array RCEN5 marker in the center of the chromosome is consistent with the position of these morphological markers in the center of the integrated genetic map of A. thaliana chromosome 5.…”
Section: Arabidopsis Thaliana Centromere Regions Genome Research 1047mentioning
confidence: 99%
See 1 more Smart Citation
“…The 180-bp array RCEN3 marker falls within this interval, ∼5.5 cM south of the GL1 genetic marker. Finally, the telocentric strategy indicated that centromere 5 is located in an ∼11-cM window between morphological markers ga-3 and tt-2 (Koornneef 1983;Hauge et al 1993). Neither of these markers is present on the current recombinant inbred genetic map, yet the localization of the 180-bp array RCEN5 marker in the center of the chromosome is consistent with the position of these morphological markers in the center of the integrated genetic map of A. thaliana chromosome 5.…”
Section: Arabidopsis Thaliana Centromere Regions Genome Research 1047mentioning
confidence: 99%
“…It is not clear whether the 180-bp repeat arrays flank or span A. thaliana centromeres, but data from mammalian systems suggest that the alphoid repeats are intimately associated with the centromere and are likely to play a role in centromere function (Heartlein et al 1988;Haaf et al 1992;Tyler-Smith et al 1993;Brown et al 1994;Larin et al 1994;Harrington et al 1997). A number of other middlerepetitive sequence elements have been found to be associated with the 180-bp repeats in genomic clones (Richards et al 1991;Schmidt et al 1995;Pelissier et al 1996; Thompson et al 1996a,b), suggesting that islands of more complex sequence arrangement are located in the A. thaliana centromeric regions.An approximate genetic location of three of the five A. thaliana centromeres (on chromosomes 1, 3, and 5) was achieved by Koornneef and coworkers using telocentric mapping techniques (Koornneef 1983; Koornneef and Van der Veen 1983). More recently, physical mapping projects have localized the centromeres on chromosomes 2 and 4 as gaps in the YAC contig maps that are bordered by genomic clones containing 180-bp repeats (Schmidt et al 1995;Zachgo et al 1996).…”
mentioning
confidence: 99%
“…Considering the number of mutations that have been isolated, this is a relatively small number of genes on the genetic map. Trisomic and telotrisomic lines have also been identified in Arabidopsis which can be used for linkage studies (Koornneef 1983 A number of different tissues of Arabidopsis including roots, leaves, stems, and seeds are susceptible to A~robacterium-mediated T-DNA transformation, (Lloyd et al 1986;Schmidt and Willmitzer 1988;Valvekens et al 1988;Feldmann and Marks 1987). (Leutwiler et al 1984;Meyerowitz and Pruitt 1985).…”
Section: -------mentioning
confidence: 99%
“…The ratio of aborted seeds produced by telotrisomic F1 plants was expected to be determined by transmission rates of monosomic and disomic gametes (Koornneef and Van der Veen 1983) and distances between the embryonic lethal and the centromere (Koornneef 1983 (Koornneef and Van·der Veen 1983).…”
Section: Backcross Analysismentioning
confidence: 99%
“…This latter assessment is based on the Buser-Kurucz (1992) model-atmosphere calculations, so it should be re-evaluated as further calculations of that kind become available. Johnson et al (1962) and Mendoza (1967) Carney (1982) and Koornneef (1983). This relation is from Taylor (1992), and is for stars with…”
Section: Appendix A: Color-index Transformationsmentioning
confidence: 94%